Osteomyelitis of the Jaw in COVID-19 Patients: A Rare Condition With a High Risk for Severe Complications - Kvolik Pavić, Ana; Zubčić, Vedran (Frontiers in Surgery, 2022)
Osteomyelitis of the jaw is an uncommon infection affecting immunocompromised and polymorbid patients that arises from the flora of the oral cavity or sinuses. Treatment includes surgical debridement and long regiments of broad-spectrum antibiotics. We present three cases of complicated jaw osteomyelitis presented with concurrent COVID-19 infection, including only two reported cases of odontogenic COVID-related osteomyelitis. The two mandibular cases were patients in their thirties, with no comorbidities. The first case was an asymptomatic COVID-19 positive patient who developed an odontogenic infection after tooth extraction which was complicated by the second bout of abscess formation and localized osteomyelitis. The second case was a COVID-19 positive patient with an odontogenic infection that presented as airway compromise due to trismus and neck edema which required an emergency tracheotomy. He developed osteomyelitis of the mandibular ramus that was reconstructed with a titanium plate. The third case was a polymorbid post-COVID-19 patient who developed a protracted infection of the maxillary sinus that resulted in the loss of an eye, destruction of the maxilla, palate, parts of nasal cavum, and oronasal incontinence. The defect was reconstructed with a microvascular anterolateral thigh flap. We hypothesize that COVID-19 related immune dysfunction and microvascular changes contributed to osteomyelitis in our patients.